TREK-1 Channel Expression in Smooth Muscle as a Target for Regulating Murine Intestinal Contractility: Therapeutic Implications for Motility Disorders - Ma, Ruolin; Seifi, Mohsen; Papanikolaou, Maria; Brown, James F.; Swinny, Jerome D.; Lewis, Anthony (Frontiers in Physiology, 2018)
Gastrointestinal (GI) motility disorders such as irritable bowel syndrome (IBS) can occur when coordinated smooth muscle contractility is disrupted. Potassium (K+) channels regulate GI smooth muscle tone and are key to GI tract relaxation, but their molecular and functional phenotypes are poorly described. Here we define the expression and functional roles of mechano-gated K2P channels in mouse ileum and colon. Expression and distribution of the K¬¬2P channel family were investigated using quantitative RT-PCR (qPCR), immunohistochemistry and confocal microscopy. The contribution of mechano-gated K2P channels to mouse intestinal muscle tension was studied pharmacologically using organ bath. Multiple K2P gene transcripts were detected in mouse ileum and colon whole tissue preparations. Immunohistochemistry confirmed TREK-1 expression was smooth muscle specific in both ileum and colon, whereas TREK-2 and TRAAK channels were detected in enteric neurons but not smooth muscle. In organ bath, mechano-gated K2P channel activators (Riluzole, BL-1249, flufenamic acid, and cinnamyl 1-3,4-dihydroxy-alpha-cyanocinnamate) induced relaxation of KCl and CCh pre-contracted ileum and colon tissues and reduced the amplitude of spontaneous contractions. These data reveal the specific expression of mechano-gated K2P channels in mouse ileum and colon tissues and highlight TREK-1, a smooth muscle specific K2P channel in GI tract, as a potential therapeutic target for combating motility pathologies arising from hyper-contractility.